Round window versus conventional bony cochleostomy technique in pediatric cochlear implantation; A Randomized controlled double blinded trial. - Shishodia, Shama; Saurav, Dipu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Objective of the study was to investigate the outcomes of cochlear implantation when done via two different techniques namely, the round window or the bony cochleostomy. Methods: A single-center, double-blinded randomized controlled trial including forty prelingual, bilateral severe to profoundly deaf children less than six years from the year 2014 to 2016 in a tertiary referral center in India were randomly allocated to round window and bony cochleostomy group. Our primary outcome measures were intraoperative neural response telemetry levels, behavioral threshold (t) and comfortable (c) loudness levels. The secondary subjective outcomes were measured via the category of auditory performance (CAP) and the meaningful auditory integration scale (MAIS) score. The cases were followed up for 9 months. Results: Intra-operative, electrically evoked compound action potentials (ECAP) showed comparable mean thresholds for both the techniques except intermediate electrodes (p 0.04) showed lower values for the round window. Similarly, a lower threshold (p 0.03) and comfortable mean current levels (p 0.03) were noticed for the round window group at 6 months post-implantation. Secondary speech perception outcome scores measured via category of auditory performance (CAP) and MAIS score were comparable. Conclusions: The round window insertion technique has physiological benefit as compared to the bony cochleostomy as evidenced by better stimulation levels in the intermediate electrodes and lower mean threshold and comfortable levels in the round window with more beneficial peri-modiolar position of electrode arrays. However, comparable speech perception outcomes revealed no clinical benefit in the cochlear implant performance depending on the technique of electrode insertion.